Perspective Planning and Policy for Commercial Energy - Planning Commission (Planning Commission, 1988)
This report has analysed the problem of choice of alternative energy resources of our country in its different regions to meet the requirements of commercial energy of the economy assuming alternative targets of rate of its growth. It has given the results of policy conclusions of this analysis. The analysis has been based on the results of a comprehensive in-depth study of the commercial energy sector using the approach of integrated energy modeling for the economy.
Planning Commission Government of India
Planning Commission Government of India